2014
DOI: 10.3109/17483107.2014.932022
|View full text |Cite
|
Sign up to set email alerts
|

The electronic, personalizable Rosetta system for dementia care: exploring the user-friendliness, usefulness and impact

Abstract: All participants found Rosetta a very useful development for future care, and would consider using it. Since Rosetta was still in development during evaluation, a discrepancy between expectations and actual functioning of Rosetta existed, which may explain the lack of findings on the impact of the system and the low appreciation of user-friendliness. Implications for Rehabilitation People with dementia and carers find assistive technology (AT) a useful future development and they are willing to use it in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
110
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(119 citation statements)
references
References 36 publications
1
110
0
8
Order By: Relevance
“…In a review of 24 studies, 64 two RCTs 65,66 and one controlled trial 67 of apps focused on cognitive training showed improved cognition, whereas one RCT did not. 68 Three other RCTs, one of serious games coupled with cognitive training, 69 one with a multicomponent program 70 and another of engagement, 71 showed no effects on various outcomes.…”
Section: Cognitive Impairmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In a review of 24 studies, 64 two RCTs 65,66 and one controlled trial 67 of apps focused on cognitive training showed improved cognition, whereas one RCT did not. 68 Three other RCTs, one of serious games coupled with cognitive training, 69 one with a multicomponent program 70 and another of engagement, 71 showed no effects on various outcomes.…”
Section: Cognitive Impairmentmentioning
confidence: 99%
“…In total, 49 studies were retrieved, 11,25-72 comprising 16 reviews 11,25,29,[31][32][33][34][35][36][37][38][39]42,51,60,64 and 33 individual studies. [26][27][28]30,40,41,[43][44][45][46][47][48][49][50][52][53][54][55][56][57][58][59][61][62][63][65][66][67][68][69][70][71][72] Key findings are presented below; more detailed evidence tables are provided in Appendix 1.…”
Section: Objective No 1: Efficacy Of Apps On Chronic Disease Self-mamentioning
confidence: 99%
“…decision support systems for guideline compliance [20]); ii) to contribute to the selfreliance of the person in need of care in such a way that direct on-site care assistance can be avoided (e.g. ambient assisted living support at home [21]); iii) to substitute the nursing support by using technology (e.g. robot that measures vital signs prior to consultation) [22]; or iv) to support the training or education of nurses (e.g.…”
Section: Definitionsmentioning
confidence: 99%
“…decision support systems for guideline compliance [20]); ii) to contribute to the self-reliance of the person in need of care in such a way that direct on-site care assistance can be avoided (e.g. ambient assisted living support at home [21]); iii) to substitute the nursing support by using technology (e.g. robot that measures vital signs prior to consultation) [22]; or iv) to support the training or education of nurses (e.g.…”
Section: Definitionsmentioning
confidence: 99%